2017
DOI: 10.1021/acs.bioconjchem.7b00252
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Size and Shape Effects on Cellular Uptake and Intracellular Distribution of siRNA Nanoconstructs

Abstract: Gold nanoparticles (AuNPs) show potential for transfecting target cells with small interfering RNA (siRNA), but the influence of key design parameters such as the size and shape of the particle core is incomplete. This paper describes a side-by-side comparison of the in vitro response of U87 glioblastoma cells to different formulations of siRNA-conjugated gold nanoconstructs targeting the expression of isocitrate dehydrogenase 1 (IDH1) based on 13-nm spheres, 50-nm spheres, and 40-nm stars. 50-nm spheres and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 48 publications
5
120
0
Order By: Relevance
“…10). 387 As mentioned in an earlier section of this review, the aggregation of NPs can change their physical properties. Therefore, TEM has been applied to characterize the dispersion of NPs after their internalization.…”
Section: Microscopy Techniques For Np Characterizationmentioning
confidence: 91%
“…10). 387 As mentioned in an earlier section of this review, the aggregation of NPs can change their physical properties. Therefore, TEM has been applied to characterize the dispersion of NPs after their internalization.…”
Section: Microscopy Techniques For Np Characterizationmentioning
confidence: 91%
“…Next, we examined the interaction of unmodified polymersomes, ssDNA-polymersomes and the small and large clusters with U87-MG glioblastoma cells, known to have a higher endocytotic potential and favor uptake of larger sized particles. 42,43 Interestingly, we observed limited internalization of both the 400 nm clusters and to a lesser extent of the larger clusters (Fig. 2D, Fig.…”
Section: Examination Of Dna-linked Polymersome Clusters' Behavior In mentioning
confidence: 72%
“…Gold nanomaterials are also accessible in many other geometries. For example, Yue et al investigated the uptake of gold nanostars (≈40 nm) in comparison to differently sized spherical particles (diameters ≈13 and 50 nm) into U87 glioblastoma cells . These studies indicated that the star shape results in an enhanced liberation of the nanostars from intracellular vesicles, which can be explained by membrane rupture processes initiated by the star spikes.…”
Section: Particle Properties and Resulting Implications On Particle–cmentioning
confidence: 99%